Impact of External Factors on Determining E-commerce Benefits among SMEs in Jakarta and Palembang - Hardiyansyah, -; Aries, -; Muchardie, Brian Garda; Rillia, Anneke (Society of Visual Informatics, 2024)
Technological trends have triggered a more advanced technology-based approach to influencing customers and encouraging the growth of the e-commerce industry in Indonesia. E-commerce is now considered a bridge for MSME players to market with a broader reach, even to international markets, which is one of the factors for the rise of Indonesian MSMEs, as well as the growth of the digital economy in Indonesia. However, very few MSMEs are still using technology to grow their business. This article examines how external factors, specifically customers and competitors, can encourage SMEs in Jakarta and Palembang to adopt e-commerce and promote e-commerce adoption. Small and medium enterprises benefit from applying this technology. The research method used was the quantitative conjoint type, using primary data in questionnaires distributed to 101 MSME owners in Jakarta and Palembang using a Google form. The data analysis technique in this study used structural equation modeling (SEM) based on partial least squares (PLS) by examining the measurement model and model structure. The results of this study indicate that perceived customer benefits have a significant influence on external relationships and are found to influence cost reduction, as well as a significant influence on loyalty. customer's status. At the same time, perceptions of competitive value increase relationships with external parties and customer loyalty. In contrast, competitive value only affects customer loyalty without significantly affecting cost reduction and external relations